Estudio de factibilidad para instalar una planta de bebidas de frutas citricas en el cantón Quevedo año 2013 - Sánchez Carreño, Yirli Yessenia (2013)
This study has allowed us to analyze the feasibility of creating a micro business that will be based on a traditional business of making fruit drinks, through a new concept with distinctive features and differentiating. The strengths of the company will be related to product and service differentiation, diversity of distribution channels, and leadership skills of the management team. Thefeaturesthattellthemicroenterprise will have aprominentpositionamong competitors, who maintain a rivalrippermiddleandhighthreat of entryofnew competitors andbarriers to entry are low. The company will havestaff with experiencein business manage mend know ledge and experience related topersonnel management, resource management, process management and experiencesinfarmingfruitcropsexistin Canton. The primary missionof the companyis to providethefruitjuicemarket, a possibilityofimmediate purchase, inseasonwhenthere is nofruit. Fruit juiceshavea largefamily consumption, with nutritionus andnaturalbenefit, thatiscraftedentirelynativefruit(green), water, sugar, citric acid, preservative andstabilizer. For the distribution and sale of this product will continue the channel intermediaries (which is sold to seconds). The business system is based on the production of fruit juices, which enables the consumer to taste this fruit rich in vitamins and natural medicinal properties if consumedfrequently. The purpose of the executive summary is to give the reader an overview and summary of the project, creating a micro to make fruit drinks in Canton Quevedo and can understand in one reading what the business, and is generated interest in the project.